RETRACTED: Immunotherapies against human bacterial and fungal infectious diseases: A review - Qadri, Hafsa; Shah, Abdul Haseeb; Alkhanani, Mustfa; Almilaibary, Abdullah; Mir, Manzoor Ahmad (Frontiers in Medicine, 2023)
Nations' ongoing struggles with a number of novel and reemerging infectious diseases, including SARS-Co-V2 outbreak, serve as proof that infectious diseases constitute a serious threat to global public health. Moreover, the fatality rate in humans is rising as a result of the development of severe infectious diseases brought about by multiple drug-tolerant pathogenic microorganisms. The widespread use of traditional antimicrobial drugs, immunosuppressive medications, and other related factors led to the establishment of such drug-resistant pathogenic microbial species. To overcome the difficulties commonly encountered by current infectious disease management and control processes, like inadequate effectiveness, toxicities, and the evolution of drug tolerance, new treatment solutions are required. Fortunately, immunotherapies already hold great potential for reducing these restrictions while simultaneously expanding the boundaries of healthcare and medicine, as shown by the latest discoveries and the success of drugs including monoclonal antibodies (MAbs), vaccinations, etc. Immunotherapies comprise methods for treating diseases that specifically target or affect the body's immune system and such immunological procedures/therapies strengthen the host's defenses to fight those infections. The immunotherapy-based treatments control the host's innate and adaptive immune responses, which are effective in treating different pathogenic microbial infections. In this review, we explore different immunotherapies and their usage for the assistance of a broad spectrum of infectious ailments caused by various human bacterial and fungal pathogenic microbes. We will discuss the recent developments in therapeutics against the growing human pathogenic microbial diseases and focus on the present and future of using immunotherapies to overcome these diseases.